Testing for Weak-Form Market Efficiency in the Botswana Stock Market - Mphoeng, Mphoeng (Archives of Business Research, 2019)
The theory of the Efficient Market Hypothesis (EMH) has been debated extensively. In this study the runs test was employed on the Botswana Stock Exchange daily Domestic Companies and Foreign Companies indices to test whether the Botswana stock market follows the random walk process and subsequently determine weak-form market efficiency. The results of the runs test showed that the indices do not follow the random walk process. As a result the Botswana stock market is determined to be weak-form market inefficient and rejects the efficient market hypothesis accordingly.